Keputusan Pembelian Ditinjau dari Viral Marketing, Kualitas Pelayanan dan Word Of Mouth Pada Resto Pawon Ayu Kartasura - Muhammad Fajar Apriyanto; Ida Aryati; Istiatin Istiatin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of viral marketing, service quality, and word of mouth on purchasing decisions at Resto Pawon Ayu Kartasura. This study uses a quantitative approach with a survey method. The population in this study is all consumers of Resto Pawon Ayu Kartasura with an unknown number, while the sampling technique uses purposive sampling with a sample size of 100 respondents. Data collection was conducted through the distribution of questionnaires using a Likert scale, then analyzed using instrument testing, classical assumption testing, and multiple linear regression analysis with the help of SPSS version 26. The results of the study indicate that viral marketing has a positive and significant effect on purchasing decisions, service quality has a positive and significant effect on purchasing decisions, and word of mouth has a positive and significant effect on purchasing decisions. Simultaneously, viral marketing, service quality, and word of mouth have a significant effect on purchasing decisions at Resto Pawon Ayu Kartasura. The coefficient of determination results show that purchasing decisions are influenced by the variables of viral marketing, service quality, and word of mouth, while the rest are influenced by other variables outside this study. This study is expected to serve as a consideration for the management of Resto Pawon Ayu Kartasura in formulating more effective marketing strategies through the optimization of viral content, improvement of service quality, and strengthening of positive recommendations from consumers in order to increase purchasing decisions.